2015
DOI: 10.2139/ssrn.2635471
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Skills on Educational Outcomes: Evidence from Performance Tests

Abstract: Digital skills are increasingly important for labor market outcomes and social participation. Do they also matter for academic performance? This paper investigates the effects of digital literacy on educational outcomes by merging data from the Italian National Assessment in secondary schools with an original data set on performance tests of Internet skills for 10 th grade students. Our identification strategy relies on a rich set of individual, family, school and classroom control variables that are not commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 48 publications
(28 reference statements)
1
16
0
7
Order By: Relevance
“…Recent studies indicate that Internet skills have a positive impact on academic achievement, with school performance being positively associated with longer Internet use for study (Kim et al 2017;Leung and Lee 2012). This effect is found to be stronger for students with low academic performance or poor socio-economic background and, conversely, for students in technical or vocational schools (Pagani et al 2016).…”
Section: (Page Number Not For Citation Purpose)mentioning
confidence: 97%
“…Recent studies indicate that Internet skills have a positive impact on academic achievement, with school performance being positively associated with longer Internet use for study (Kim et al 2017;Leung and Lee 2012). This effect is found to be stronger for students with low academic performance or poor socio-economic background and, conversely, for students in technical or vocational schools (Pagani et al 2016).…”
Section: (Page Number Not For Citation Purpose)mentioning
confidence: 97%
“…However, the presence of ICT in the classroom is likely to facilitate a debate between students and their teachers on digital risks and opportunities, whose level of awareness seem particularly poor among adolescents (Calvani et al 2012, Gui and Argentin 2011, Van Deursen and van Dijk 2009). Furthermore, there is evidence that digital supportive teachers tend to have more digitally aware students (Argentin et al 2013) and that, in turn, a higher level of students' critical digital skills has a positive impact on their learning outcomes (Pagani et al 2015).…”
Section: Table 3 Around Herementioning
confidence: 99%
“…In Chile, a high school study measured frequency of computer activities using a 4‐point scale where 1 = never, 2 = monthly, 3 = weekly and 4 = every day (Hinostroza et al , ). Finally, a recent study of data from the Italian National Assessment found that Internet skills positively impact student achievement (Pagani, Argentin, Gui, & Stanca, ). Therefore, frequency of Web 2.0 use was the ultimate endogenous variable.…”
Section: Theoretical Background and Research Questionsmentioning
confidence: 99%